2015
DOI: 10.1021/cb501004q
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potent Phosphodiesterase Inhibitors that Demonstrate Cyclic Nucleotide-Dependent Functions in Apicomplexan Parasites

Abstract: Apicomplexan parasites, including Plasmodium falciparum and Toxoplasma gondii, the causative agents of severe malaria and toxoplasmosis, respectively, undergo several critical developmental transitions during their lifecycle. Most important for human pathogenesis is the asexual cycle, in which parasites undergo rounds of host cell invasion, replication, and egress (exit), destroying host cell tissue in the process. Previous work has identified important roles for Protein Kinase G (PKG) and Protein Kinase A (PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
114
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(121 citation statements)
references
References 33 publications
7
114
0
Order By: Relevance
“…Because PKG is activated by the second messenger cGMP, compounds that elevate cGMP levels should stimulate microneme secretion. Consistent with studies showing that zaprinast, an inhibitor of cGMPPDEs, stimulates egress (9), it was later shown that zaprinast stimulates microneme secretion in Toxoplasma, presumably by elevating cGMP (16 min stimulates microneme secretion by activating PKG via increasing cGMP levels. To determine whether serum albumin affects cGMP levels, RH-MIC2-GLuc-C-myc parasites were mock-treated or treated with serum albumin.…”
Section: Mic2-gluc-c-myc Is a Highly Sensitive Reporter Of Microneme supporting
confidence: 73%
See 1 more Smart Citation
“…Because PKG is activated by the second messenger cGMP, compounds that elevate cGMP levels should stimulate microneme secretion. Consistent with studies showing that zaprinast, an inhibitor of cGMPPDEs, stimulates egress (9), it was later shown that zaprinast stimulates microneme secretion in Toxoplasma, presumably by elevating cGMP (16 min stimulates microneme secretion by activating PKG via increasing cGMP levels. To determine whether serum albumin affects cGMP levels, RH-MIC2-GLuc-C-myc parasites were mock-treated or treated with serum albumin.…”
Section: Mic2-gluc-c-myc Is a Highly Sensitive Reporter Of Microneme supporting
confidence: 73%
“…Consistent with this finding, cyclic GMP (cGMP) has emerged as a second signaling molecule that stimulates microneme secretion. Indirect evidence for this pathway is provided by inhibitors of cGMP-specific phosphodiesterases (PDE), such as zaprinast and BIPPO, which stimulate microneme secretion and egress in Toxoplasma (9,16), and Plasmodium falciparum merozoites (17). More directly, chemical-genetic studies showed that inhibition of PKG blocks microneme secretion in Eimeria tenella sporozoites (15), Toxoplasma tachyzoites (15), and P. falciparum merozoites (17).…”
mentioning
confidence: 99%
“…Microneme secretion is controlled by two key signaling pathways, calcium (Ca 2+ ) and cyclic GMP (cGMP), which direct calcium-dependent protein kinases (CDPKs) (6) and protein kinase G (PKG) (7, 8), respectively, to transduce their respective signals through substrate phosphorylation. Phosphoproteomic studies have identified substrates for CDPK1 in T. gondii (9) and PKG in Plasmodium spp.…”
Section: Introductionmentioning
confidence: 99%
“…In Trypanosoma cruzi , an ortholog of huPDE4, TcPDE4 (TcPDEB1) displayed an inhibition profile characteristic of the PDE4 subfamily, including a specificity for cAMP over cGMP [62]. Lastly, PDE inhibitors block the in vitro proliferation of Plasmodium falciparum and Toxoplasma gondii [63, 64]. …”
Section: Introductionmentioning
confidence: 99%